A study of the recordkeeping practices of Victory Christian Fellowship (VCF) - Jimenez, Giselle M.; Buenrostro, Iyra S.; Victory Christian Fellowship (2010.)
Just like organizations that conduct business and operations, churches also produce records that document their own operations. It is in this light that this study focused on the recordkeeping practices of Victory Christian Fellowship (VCF). Thirty local churches were surveyed as to how they manage their records according to the three stages of the Records Life Cycle. A focus group discussion (FGD) with Church Secretaries and interviews with the staff of Victory Ministers Association were likewise conducted to yield more accurate results on how the local churches manage their records.
The data gathered from the survey questionnaire and interviews revealed that there is a shortage of staff in each local church that contributes to neglect in the proper management of their records.
It was also discovered that the lack of standard practices and guidelines result to each local church managing records their own way. The practices they employ on managing their records fall short of the best practices as prescribed by various literature on Records Management. In addition to these, it was found out that this scenario results in various and interrelated problems local churches face with their records.
Recommendations cited included adopting a culture of Records Management; designing and implementation of a Records Management System, as prescribed by ISO 15489-2001;creating a Records Center and documenting a congregational history of each local church. A list of proposed best practices was likewise included, the contents of which will be printed in a manual that will be distributed to the local churches.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Records -- Management -- Philippines; Church records and registers -- Philippines